The desmosomal cadherin desmoglein-3 acts as a keratinocyte anti-stress protein via suppression of p53 - Rehman, Ambreen; Cai, Yang; Hünefeld, Christian; Jedličková, Hana; Huang, Yunying; Teck Teh, Muy; Sharif Ahmad, Usama; Uttagomol, Jutamas; Wang, Ying; Kang, Angray; Warnes, Gary; Harwood, Catherine; et al. (Cell death & disease, 2019)
Desmoglein-3 (Dsg3), the Pemphigus Vulgaris (PV) antigen (PVA), plays an essential role in keratinocyte cell-cell adhesion and regulates various signaling pathways involved in the progression and metastasis of cancer where it is upregulated. We show here that expression of Dsg3 impacts on the expression and function of p53, a key transcription factor governing the responses to cellular stress. Dsg3 depletion increased p53 expression and activity, an effect enhanced by treating cells with UVB, mechanical stress and genotoxic drugs, whilst increased Dsg3 expression resulted in the opposite effects. Such a pathway in the negative regulation of p53 by Dsg3 was Dsg3 specific since neither E-cadherin nor desmoplakin knockdown caused similar effects. Analysis of Dsg3-/- mouse skin also indicated an increase of p53/p21WAF1/CIP1 and cleaved caspase-3 relative to Dsg3+/- controls. Finally, we evaluated whether this pathway was operational in the autoimmune disease PV in which Dsg3 serves as a major antigen involved in blistering pathogenesis. We uncovered increased p53 with diffuse cytoplasmic and/or nuclear staining in the oral mucosa of patients, including cells surrounding blisters and the pre-lesional regions. This finding was verified by in vitro studies where treatment of keratinocytes with PV sera, as well as a characterized pathogenic antibody specifically targeting Dsg3, evoked pronounced p53 expression and activity accompanied by disruption of cell-cell adhesion. Collectively, our findings suggest a novel role for Dsg3 as an anti-stress protein, via suppression of p53 function, and this pathway is disrupted in PV.
Keywords: kaspasa 3; pemfigus; Animals; Stress, Physiological; Tumor Suppressor Protein p53; keratinocyty; proteolýza; Proteolysis; desmoglein 3; leupeptiny; Keratinocytes; lidé; Mice; Antibodies; kůže; Dogs; kultivované buňky; myši; fyziologický stres; Cells, Cultured; Desmoglein 3; desmozomy; Pemphigus; Skin; Leupeptins; nádorový supresorový protein p53; Caspase 3; zvířata; psi; protilátky; Desmosomes; Humans